Evaluation of Effects of Unethical Practices on Cost and Time Performance of Construction Projects in Tertiary Institutions in Edo State, Nigeria - Momodu, Aliu Salumanu; Olusola, Akinradewo Festus; Temitope, Arijeloye Bamidele; Treasure, Ijieh Oriabure (International Journal of Project Management, 2024)
Purpose: Unethical practices in the construction sector have dire consequences for effective delivery of projects and trickling down to the poor performance of construction projects. This research evaluated the effects of unethical practices on cost and time performance of construction projects in tertiary institutions in Edo State, Nigeria. Materials and methods: Respondents were drawn from a public tertiary institution in the State, which was the focus of the study. The study adopted a mixed method design of quantitative and qualitative approaches. 30 questionnaires were self-administered by census on identified human samples. Thereafter, semi-structured interview questions were used purposively to elicit relevant information from 5 targeted participants to validate the data received. The data received were analyzed using regression analysis and paired samples t- test. Microsoft Excel and Statistical Package for Social Sciences (SPSS) version 23 was used to carry out the analyses. Findings: It was established that there was a significant relationship between unethical practices and project performance. It was also established that the projects performed well in terms of costs but performed poorly in terms of time. Implications to Theory, Practice and Policy: The study further established that the predominant effect of unethical practices on performance of tertiary institution projects in Edo State is time-overrun.